More than Decoration: Roles for Natural Killer Group 2 Member D Ligand Expression by Immune Cells - Trembath, Andrew P.; Markiewicz, Mary A. (Frontiers in Immunology, 2018)
The activating immune receptor natural killer group 2 member D (NKG2D), which is expressed by NK cells and T cell subsets, recognizes a number of ligands expressed by “stressed” or damaged cells. NKG2D has been extensively studied for its role in tumor immunosurveillance and anti-viral immunity. To date, the majority of studies have focused on NKG2D-mediated killing of target cells expressing NKG2D ligands. However, with a number of reports describing expression of NKG2D ligands by cells that are not generally considered stressed, it is becoming clear that some healthy cells also express NKG2D ligands. Expression of these ligands by cells within the skin, intestinal epithelium, and the immune system suggest other immune functions for NKG2D ligand expression in addition to its canonical role as a “kill me” signal. How NKG2D ligands function in this capacity is just now starting to be unraveled. In this review we examine the expression of NKG2D ligands by immune cells and discuss current literature describing the effects of this expression on immunity and immune regulation.